2019
DOI: 10.1002/mrc.4810
|View full text |Cite
|
Sign up to set email alerts
|

D‐HMBC versus LR‐HSQMBC: Which experiment provides theoretically and experimentally the best results?

Abstract: The long‐range heteronuclear single quantum multiple bond correlation (LR‐HSQMBC) experiment is the experiment of choice for visualizing heteronuclear long‐range coupling interactions nJCH across 4–6‐bonds and is experimentally superior to the decoupled heteronuclear multiple‐bond correlation (D‐HMBC) experiment. Yet, the exact reasons have not been fully understood and established. On the basis of our recent investigation of the nonrefocused variants LR‐HSQC and HMBC, we have extended a JHH′‐dedicated investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…and proved to be the best choice for detecting very weak long-range correlations. [4,9,[18][19][20][21][22][23] However, and despite the absence of J HH 0 -modulation our recent findings demonstrate that in LR-HSQC experiments, the intensity of the long-range cross peaks is influenced in an unwanted way by the magnitude and number of passive homonuclear proton-proton couplings J HH 0 . [24] In addition, there are two other, long known, disadvantages associated with LR-HSQC spectra: (i) The information density in LR-HSQC spectra due to the large number of detectable n J CH correlations can be too high and therefore confusing.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…and proved to be the best choice for detecting very weak long-range correlations. [4,9,[18][19][20][21][22][23] However, and despite the absence of J HH 0 -modulation our recent findings demonstrate that in LR-HSQC experiments, the intensity of the long-range cross peaks is influenced in an unwanted way by the magnitude and number of passive homonuclear proton-proton couplings J HH 0 . [24] In addition, there are two other, long known, disadvantages associated with LR-HSQC spectra: (i) The information density in LR-HSQC spectra due to the large number of detectable n J CH correlations can be too high and therefore confusing.…”
Section: Introductionmentioning
confidence: 56%
“…Of note, selective and nonselective versions of the LR‐HSQMBC pulse sequence, a refocused variant of the LR‐HSQC experiment, have been recently proposed and proved to be the best choice for detecting very weak long‐range correlations. [ 4,9,18–23 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not detailed here, a similar behavior would also occur with the refocused version of the HMBC experiment. 6 Other illustrative simulations with other spin systems can be found in the Supporting Information (Figures S1 and S2). In analogy, Figure S3 shows the theoretical signal behavior for cross-peaks with an n J CH of 2 and 8 Hz as a function of the passive J HH′ in HSQMBC and selHSQMBC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The use of refocused versions of these experiments has been reported to improve the observation of IP magnetization components that can be detected under heteronuclear decoupling. Recently, a comparative study focusing on the effects of J HH modulation in D‐HMBC versus LR‐HSQMBC pulse schemes concluded that more cross‐peaks are expected to show up in an LR‐HSQMBC spectrum compared with a D‐HMBC spectrum . In particular, the use of ultra‐long‐range correlations observed in LR‐HSQMBC spectra has shown its usefulness in computer‐assisted structure elucidation (CASE) analysis of proton‐deficient natural products .…”
Section: Figurementioning
confidence: 99%
“…Recently, a comparative study focusing on the effects of J HH modulation in D-HMBC [4] versus LR-HSQMBC [5][6] pulse schemes concluded that more cross-peaks are expected to show up in an LR-HSQMBC spectrum compared with a D-HMBC spectrum. [7][8] In particular, the use of ultra-long-range correlations observed in LR-HSQMBC spectra has shown its usefulness in computer-assisted structure elucidation (CASE) analysis of proton-deficient natural products. [9] On the other hand, HSQMBC-TOCSY [10] and ADEQUATE experiments [11][12] are alternative NMR tools to detect such longer-range correlations, although the limitations in sensitivity due to additional relaxation effects or the required 13 C-13 C selection at natural abundance are challenges to overcome.The advantages of using a 1 H frequency-selective version of the HSQMBC experiment (selHSQMBC) that has been previously reported to measure n J CH coupling constants from pure absorption IP coupling J patterns is analyzed herein.…”
mentioning
confidence: 99%